2014
DOI: 10.1159/000369013
|View full text |Cite
|
Sign up to set email alerts
|

GPR30 Gene Polymorphisms Are Associated with Gynecomastia Risk in Adolescents

Abstract: Aim: The G protein-coupled receptor, GPR30, which is a third estrogen receptor, has been shown to mediate estrogenic effects on the essential features of human breast cancer cells. The aim of this study was to evaluate the association between GPR30 single nucleotide polymorphisms and gynecomastia in males. Methods: This study included 109 male adolescents with gynecomastia and 104 controls. Follicle stimulating hormone, luteinizing hormone, total testosterone, estradiol (E2), dehydroepiandrosterone sulfate (DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The GG genotype of both the rs3808350 and rs3808351 polymorphisms and GGC haplotype increased the risk of developing leiomyoma. Our findings are consistent with those of Korkmaz et al [28] and with the SNP location, which might explain the changes in GPR30 expression described by Tian et al [19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The GG genotype of both the rs3808350 and rs3808351 polymorphisms and GGC haplotype increased the risk of developing leiomyoma. Our findings are consistent with those of Korkmaz et al [28] and with the SNP location, which might explain the changes in GPR30 expression described by Tian et al [19].…”
Section: Discussionsupporting
confidence: 93%
“…Chevalier et al [27] demonstrated that the GG genotype in both the rs3808350 and rs3808351 polymorphisms protected against seminoma in Caucasian males. Finally, Korkmaz et al [28] reported that the GG genotype of rs3808350, AA Statistically significant results are shown in bold genotype of rs3808351, G allele of rs3808350, and A allele of rs3808351 increased the risk of gynecomastia in a Turkish population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Applying "reverse translational medicine" we should rethink our therapeutic approaches when using these drugs which also suggest possible new therapeutic indications such as for the treatment of bleeding in hereditary heamorrhagic telangiectasia [182] and possibilities for future drug development. Medical genetics studies have found that genetic polymorphisms of GPER are associated with changes in cell function [183] or disease susceptibility for dyslipidemia [73], arterial hypertension [108], seminoma [184], gastric cancer [185], breast cancer [186], leiomyoma [187] and gynecomastia in adolescents [188] providing us with new opportunities for personalized medicine, theranostics, and thereby improving treatment and prevention. Continued clinical research is required to increase our understanding of estrogen receptors and the clinically approved drugs targeting them and how these drugs mediate therapeutic benefits and unwanted side effects in patients, which ultimately will improve patient safety and survival.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed medical records of patients and compared the distribution of the genotype and allele frequencies of fourteen (14) GPR30 SNPs in patients with and without ovarian cancer.…”
Section: Study Design and Populationmentioning
confidence: 99%